Hearing Anatomy, Physiology, and Disorders of the Auditory System - Moller, Aage R. (Elsevier Science, 2006)
Hearing: Anatomy, Physiology and Disorders of the Auditory System provides detailed information about the anatomy and physiology of the entire auditory system and it describes important aspects of disorders of the middle ear, the cochlea, and the nervous system in a comprehensive manner. Most other textbooks on Hearing are focused on either the periphery or the central nervous system and rarely integrate anatomy and physiology with clinical issues. In the past years, it has become apparent that pathologies of the peripheral parts of the auditory system affect the function of the nervous system, and vice versa. It is thus more and more important to view the peripheral and central parts of the auditory system in an integrative way. This book integrates descriptions of disorders of the ear and the nervous system and provides a comprehensive coverage of anatomy and physiology of the entire auditory system. The book introduces the role of neural plasticity in the symptoms of disorders such as tinnitus, hyperacusis and phonophobia. A separate chapter discusses cochlear and auditory brainstem implants. · This book provides a thorough understanding of the anatomy and function of the auditory system · Provides thorough information on the peripheral nervous system and auditory organs as well as the central nervous system · As valuable for students of and reasearchers in basic sciences (biology, psychology, neuroscience, audiology etc) as for clinicians · Offers an introduction into psychoacoustics and physical acoustics · Presents information on important disorders of the auditory system (including Tinnitus, · Includes chapter on cochlear and auditory brainstem implants · Fully illustrated with carefully selected images